THE FORBIDDEN SONGS - Varna Marianne Nielsen 1981- (2024)
This practise-based research project aims to convey the traditional Greenlandic social, spiritual, intellectual, and artistic practice, drumdancing and drumsinging, from the perspective of a practitioner, through a film. Secondary, to create a website, to gather my portfolio, of current and future research projects. (www.qilaat.org.) Categorised as a performative documentary, the film “The forbidden songs” is based on the filmmaker´s ethnographic research and artistic experience combined with qualitative studies of multiple Greenlandic Inuit drumdancers, cultural knowledge keepers weaved into archival material. This is the first of four chapters, which focuses on the historical aspect of drumdancing, beginning from the pre-colonial times citing the colonial era up until today. The film emphasizes the importance of revival of a cultural tradition, the once forbidden songs and its significance to the Inuit in Greenland. In this reflective report I will engage you in the process of gathering and assembling the pieces to convey and contract a broad amount of information while bridging personal narratives with archival material. I am grateful to Inukitsoq Sadorana (Qaanaaq), Mikkel Bianco (Tasiilaq) Tukummeq Qaavigaaq (Qaanaaq), James Ignatiussen (Tasiilaq), Aanganni Mikaelsen (Tasiilaq) and Vittus Mathiassen (Tasiilaq) and Kalaallit Nunaata Radioa (KNR) for their contributions to this film. I learned a lot through their individual stories, and most important how the changes and loss of heritage in Greenland, affected everyone. It made the purpose of finding new ways of sharing our traditional practice, even more relevant and urgent. Furthermore, we articulated the purpose of the ancient tradition, consequences of colonization/danization and re-introduced the traditional way to heal through the practice of drumdancing and drumsinging. The film is in Greenlandic, with English subtitles.